Environmental impact and economic benefit evaluation of sewage sludge treatment technologies. Issue 3 (February 2020) - Yang, Xiyue; Mu, Hailin; Zhao, Heran; Xue, Zhaoquan; Li, Nan
Abstract: In order to evaluate the environmental and economic performance of continuous thermal hydrolysis (CTH) of sludge disposal, we compare the CTH with three traditional technologies including anaerobic digestion, aerobic composting and dry-incineration. This study uses life cycle assessment (LCA) to assess their environmental impact of the above technologies, and selects ten characteristic indicators from e-Balance analysis software for quantification. We also adopt the cost-benefit ratio (B/C) to evaluate the technologies' economic performances, and come to conclusion that the larger the value is, the more economically feasible it will be. The results show that, as a new sludge disposal technology, CTH has the best performance in both environmental and economic aspects, while dry-incineration and anaerobic digestion have the worst results in environmental and economic aspect respectively. Although sludge compost has a moderating effect on global warming, it could also be potentially toxic. Nevertheless, the use of raw materials and energy contributes significantly to the environmental impact of each scheme.